METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENDUKUNG KEPUTUSAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (PNPM-MP) (Studi Kasus di Kelurahan Bahkapul Kecamatan Siantar Sitalasari Kota Pematangsiantar Provinsi Sumatera Utara) - Edison Ulung Panggabean Simanihuruk; Arifin Tua Purba (Politeknik Bisnis Indonesia, 2019)
The National Urban Independent Community Empowerment Program (PNPM-MP) in practice involves many elements in the field, such as communities, government, PNPM officers and community institutions with the types of activities in the form of environmental, social and economic activities. Community participation in the entire PNPM-MP process is very important to be assessed and measured so that it can be accounted for. Community participation in empowerment programs should cover the entire process from the beginning to the final stage. Community participation can occur in 4 (four) levels, namely Participation in the decision-making process, Participation in implementation, Participation in the utilization of results and Participation in evaluation. To get the priority of community participation in supporting PNPM-MP in the Bahkapul Urban Village, Siantar Sitalasari District, Pematangsiantar City, North Sumatra Province, a solution was needed. The solution is a decision support system (SPK). The decision support system applies the Analytical Hierarchy Process (AHP) method by arranging a hierarchical structure to determine the problem and its objectives, determining and giving weight to each criterion and subcriteria so that each alternative involved in the decision support system can be analyzed accurately. The results of the study are that the decision support system can provide appropriate recommendations to decision makers in determining and realizing the National Independent Community Empowerment Program (PNPM-MP) in Bahkapul Sub-District, Siantar Sitalasari District, Pematangsiantar City, North Sumatra Province.